Hegemoni Ideologi Penguasa Terhadap Guru Pendidikan Kewarganegaraan - Zulkarnain (Jurnal Ilmiah Mimbar Demokrasi, 2020)
This paper wishes to conduct a critical analysis of Citizenship Education in Singapore. Citizenship education as one of the national agenda in Singapore has an important position in providing citizenship understanding in order to prepare young citizens for the future of Singapore. Singapore's centralized education system and strict controls lead to highly vulnerable citizenship education politicization and ideologization of citizens through education. In fact, many studies show that the government under the People's Action party (PAP) is using authoritarian ways to defend and perpetuate its power through education. The attempts by the Singapore government with the soft authoritarian government or some experts say authoritarian with the usual Gramscian meaning "hegemony". Hegemony is the effort of a person or group of people (state) in maintaining or dominating his power in a peaceful way not by violence. With literature research and critical analytical descriptive methods in the form of relevant books and research, this paper wants to show how the PAP seeks to interpret its ideology with the hegemony done to teachers of citizenship education. The study concludes that not all teachers are hegemonized by Singapore's strict citizenship education policy.